2019
DOI: 10.3390/pathogens8030149
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Transmission at Low Temperature by Aedes albopictus Mosquitoes

Abstract: Aedes albopictus is an important vector of chikungunya virus (CHIKV). In Australia, Ae. albopictus is currently only known to be present on the islands of the Torres Strait but, should it invade the mainland, it is projected to spread to temperate regions. The ability of Australian Ae. albopictus to transmit CHIKV at the lower temperatures typical of temperate areas has not been assessed. Ae. albopictus mosquitoes were orally challenged with a CHIKV strain from either Asian or East/Central/South African (ECSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…A higher percentage of cases was observed in adult females (56.7%) than males (38%) and female children (43.3%). However, previously published reports have indicated that both sexes suffer equal burdens of the disease [36,37]. The higher percentage of adult female cases may be due to higher levels of exposure to infected vectors in the home environment since Bengali women spend more time at home, and the mosquitoes are commonly found indoors [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A higher percentage of cases was observed in adult females (56.7%) than males (38%) and female children (43.3%). However, previously published reports have indicated that both sexes suffer equal burdens of the disease [36,37]. The higher percentage of adult female cases may be due to higher levels of exposure to infected vectors in the home environment since Bengali women spend more time at home, and the mosquitoes are commonly found indoors [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti mosquitoes were orally infected with a CHIKV strain from the Asian genotype (GenBank accession MF773560) and held at 18, 28 or 32 °C for either 3- or 7-days post infection (dpi) (n=18-20 mosquitoes per combination of T °C and dpi). Using qRT-PCR (as per [26]), we found that at 3 dpi, the number of virus genome copies in mosquito bodies (including heads but without wings and legs) held at 32 °C was significantly higher than that from mosquitoes held at the other temperatures ( Fig. 1 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Five to 7-day old Ae. aegypti were orally challenged with virus-infected or sheep blood alone (control), using methods previously described [26]. A CHIKV strain from the Asian Genotype (GenBank ID: MF773560) was prepared as described in [26] and delivered in oral feeds at a final pfu of 1 × 10 7 per ml of virus stock.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First described as temperature dependent by Davis in 1932 ( Davis, 1932 ), EIP is often used as an index of vector competence. Higher temperatures are associated with reduced EIP and enhanced vector competence in many virus-vector pairings ( Chamberlain and Sudia, 1955 ; Richards et al, 2007 ; Xiao et al, 2014 ; Liu et al, 2017 ; Wimalasiri-Yapa et al, 2019 ; Winokur et al, 2020 ). Virus replication rates generally increase with temperature, and since dissemination and transmission correlate with viral load ( Kramer and Ciota, 2015 ), lower temperature is generally less advantageous for arbovirus transmission.…”
Section: Temperature and Its Potential To Influence Arboviruses Transmentioning
confidence: 99%